Ameloblastic fibrosarcoma of the mandible: A case report and mini review - HU, YUAN-YUAN (D.A. Spandidos, 2014)
Ameloblastic fibrosarcoma (AFS) is a rare malignant odontogenic neoplasm of the jaw. AFS is characteristically composed of a benign odontogenic epithelium and a malignant mesenchymal component. The posterior region of the mandible is the predominantly occupied site. In the present report, a new case of AFS in a 22-year-old male that originated from ameloblastic fibroma was described. Histologically, the tumor showed biphasic components: Benign epithelium and a malignant mesenchymal component. Immunochemical findings revealed that the tumor cells were positive for cluster of differentiation (CD) 34, vimentin, Ki-67 and p53, but negative for smooth muscle actin, S-100, CD68 and desmin. The clinical presentation, radiographic appearances and treatment measures were additionally described and reviewed.